Rare Case of Duodenal Metastasis From Colon Cancer: Review of Literature and Insights on Novel Therapies - Ammar Ismail; William K. B. Boateng; Amira Alnakeb; Youssef Botros; Allan L. Cruz (Case Reports in Gastrointestinal Medicine, 2025)
Metastasis to the duodenum from colorectal cancer is exceptionally rare and presents significant diagnostic and therapeutic challenges. We describe a 68-year-old female with right colon adenocarcinoma, who developed a duodenal metastasis despite treatment with FOLFOX chemotherapy. Transition to FOLFIRI yielded limited success, emphasizing the need for innovative approaches. Genetic analysis revealed a KRAS G12D mutation, for which targeted therapies are not yet approved. Immunohistochemistry confirmed the gastrointestinal origin of the duodenal mass. Literature indicates that surgical resection can offer curative potential in select cases, although it was not viable here. Emerging KRAS-targeted agents, such as MRTX1133, represent promising options for addressing this mutation. This case underscores the challenges of managing rare metastatic patterns, the potential of personalized therapies, and the necessity for further research into innovative treatments for advanced colorectal cancer. It highlights the importance of developing targeted strategies to improve outcomes for patients with such complex metastatic diseases.